Enhancing High School Students' Problem-Solving Skills Through Digital Module Integration - Rahmatullah, Putera Islamiyadi; Akhyar, Muhammad; Efendi, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
In programming education, problem-solving skills are essential for high school students to understand and apply coding concepts effectively. Traditional teaching methods often lack interactive elements, making it difficult for students to engage with complex programming concepts. Digital modules offer an interactive and structured learning approach that can enhance students' engagement and cognitive abilities in problem-solving. This study aimed to evaluate the effectiveness of digital modules in enhancing high school students’ problem-solving skills in programming education. A quasi-experimental design with pre-test and post-test assessments was used to compare the outcomes between experimental and control groups. The study involved 60 high school students, divided into two groups: 30 students in the experimental group using digital modules and 30 in the control group relying on conventional methods such as lectures and PowerPoint presentations. The digital module was designed with structured tasks and collaborative coding activities to support analytical thinking and practical problem-solving. Data analysis, including independent sample t-tests and N-Gain calculations, demonstrated a significant improvement in the experimental group’s problem-solving performance. The experimental group achieved an N-Gain score of 85.2%, categorized as